2018
DOI: 10.1111/bjop.12288
|View full text |Cite
|
Sign up to set email alerts
|

A moderate financial incentive can increase effort, but not intelligence test performance in adult volunteers

Abstract: A positive correlation between self-reported test-taking motivation and intelligence test performance has been reported. Additionally, some financial incentive experimental evidence suggests that intelligence test performance can be improved, based on the provision of financial incentives. However, only a small percentage of the experimental research has been conducted with adults. Furthermore, virtually none of the intelligence experimental research has measured the impact of financial incentives on test-taki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…It is common not to provide monetary incentives during the RSPM test in the psychology and psychometric studies (Gill and Prowse ). Furthermore, previous studies observed no significant effect of financial incentives on performance of intelligence test (Borghans, Meijers, and Ter Weel ; Gignac ).…”
mentioning
confidence: 68%
“…It is common not to provide monetary incentives during the RSPM test in the psychology and psychometric studies (Gill and Prowse ). Furthermore, previous studies observed no significant effect of financial incentives on performance of intelligence test (Borghans, Meijers, and Ter Weel ; Gignac ).…”
mentioning
confidence: 68%
“…A number of nonintellective factors (e.g., competitiveness, compliance with authority), and in particular test-taking motivation, have been theorized and/or shown empirically to be related to psychometric intelligence (Revelle, 1993; Wechsler, 1943; Wise, 2009). In the areas of educational and industrial psychology, a nonnegligible amount of research has substantiated a positive association (≈.20 to .25) between individual differences in test-taking motivation/effort and psychometric intelligence (Duckworth, Quinn, Lynam, Loeber, & Stouthamer-Loeber, 2011; Gignac, 2018; Hopfenbeck & Kjærnsli, 2016; Schiel, 1996; Thelk, Sundre, Horst, & Finney, 2009). Consequently, researchers and practitioners have expressed concerns about the possibility that intelligence test scores may be contaminated by individual differences in test-taking motivation (Wise, 2009).…”
Section: Background: Theory and Measuresmentioning
confidence: 99%
“…Consistent with the theory above, most of these studies have found that monetary incentives trigger more effort. However, several have found that this effort has failed to translate into better performance (see, e.g., Chowdhury & Karakostas, 2020; Cole et al, 2018; Etchart-Vincent, 2006; Gignac, 2018; Huillery & Seban, 2021; Mohd-Sanusi and Mohd-Iskandar, 2007).…”
Section: Concepts and Literature Reviewmentioning
confidence: 99%
“…Studies have measured cognitive effort in different ways. Some studies use measures that are closely related to the performance of the individual (e.g., the amount of time spent in the task; see, for example, Konheim-Kalkstein and van den Broek, 2008; Meloy et al, 2006; Mohd-Sanusi and Mohd-Iskandar, 2007) or self-reported scales (Belle & Cantarelli, 2015; Cole et al, 2018; Gignac, 2018). Other studies rely on pupillometry measures as these indicate increases in short-term memory demand (Eckstein et al, 2017; Piquado et al, 2010; van der Wel & van Steenbergen, 2018).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation